The Role of the Kamsel Unit Through Land Community Education in Reduce Traffic Affects in the Jurisdiction of the Pati Police Department - Muhammad Adib Faqihan Yusuf (Advances in Police Science Research Journal, 2022)
The high traffic violations that occur in the Pati Police Legal Area due to a lack of awareness of traffic by the community in the Pati Police jurisdiction are the background for the implementation of Traffic Community Education activities by the Pati Satlantas Satlantas Unit. This final project aims to find out what roles have been carried out by the Kamsel Unit so far in reducing violations in the Pati Police Legal Territory, what factors have influenced the activities of Societies Education, and the efforts carried out by the Kamsel Unit through Community Education activities. reduce traffic violations. This research uses a qualitative approach with the type of field research research by conducting limited observations, interviewing resource persons and document studies. In addition, the data used is also obtained from various references such as articles, journal books and relevant online media news. This study uses management theory and communication theory as well as the concepts contained in the laws and regulations governing Road Traffic and Transportation (LLAJ). The Satlantas Satlantas Unit of Pati Police carries out Society Education activities as a pre-emptive and preventive measure to prevent traffic violations. The occurrence of traffic violations is due to a lack of public awareness of traffic order in the Pati Police jurisdiction. In addition, the lack of public reluctance towards the police makes people disobedient to traffic regulations. The inhibiting factors for Community Education Then, namely the ability to communicate with Dikyasa Unit personnel, inadequate infrastructure, less up-to-date delivery methods and poor public enthusiasm. The efforts made by the Dikyasa Unit are through coaching and counseling, safety riding, integration of traffic materials in the education curriculum. Based on this, it is hoped that the Satlantas Satlantas unit of Pati Police will improve and maximize the performance of each activity carried out by making the implementation of Society Education more interesting so that it can attract the enthusiasm of the community in the Pati Police jurisdiction.